Enteral nutrition provided within 48 hours after admission in severe acute pancreatitis: A systematic review and meta-analysis. Issue 34 (August 2018) - Song, Jianbo; Zhong, Yilong; Lu, Xiaoguang; Kang, Xin; Wang, Yi; Guo, Wenxiu; Liu, Jie; Yang, Yilun; Pei, Liying
Abstract: Background: Whether to conduct enteral nutrition in patients with severe acute pancreatitis (SAP) during the active phase of intestinal stress or to feed during remission remains controversial. This study was aimed to evaluate the efficacy and safety of enteral nutrition within 48 hours after admission in the patients with SAP or predicted severe acute pancreatitis (pSAP). Methods: We searched PubMed, EMBASE, Web of Science, and the Cochrane Library before December 2017. Randomized controlled trials of early enteral nutrition (starting within 48 hours after admission) versus late enteral nutrition or total parental nutrition in severe acute pancreatitis or predicted severe acute pancreatitis were selected. Results: Ten randomized controlled trials containing 1051 patients were included. Comparing early enteral nutrition to late enteral nutrition or total parental nutrition in SAP or pSAP, the pooled risk ratios were 0.53 (95% confidence interval [CI] 0.35–0.81, P = .003) for mortality, 0.58 (95% CI 0.43–0.77, P = .0002) for multiple organ failure (MOF), 0.50 (95% CI 0.33–0.75, P = .0008) for operative intervention, 0.75 (95% CI 0.61–0.93, P = .009) for systemic infection, 0.42 (95% CI 0.26–0.69, P = .0005) for local septic complications, 0.84 (95% CI 0.74–0.96, P = .01) for gastrointestinal symptoms. 0.87 (95% CI 0.74–1.02, P = .08) for systemic inflammatory response syndrome (SIRS), and 1.24 (95% CI 0.66–2.31, P = .50) for other local complications. Conclusions: Enteral nutrition within 48 hours after admission is efficient and safe for the patients with SAP or pSAP. Abstract : Supplemental Digital Content is available in the text